Analisis Rasio Keuangan untuk Memprediksi Pertumbuhan Laba Perusahaan PT Bank Negara Indonesia (BNI) Syariah TBK - Salim, Agus; Rimawan (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
Abstract The purpose of this study was to determine and analyze the effect of Return On Asset (ROA) on Profit Growth at sharia Bank Negara Indonesia. This study is with a population of 9 years. While the sample of this study was determined using Purposive sampling with an observation period 2014 – 2018. The analysis technique used was Simple Linier Regression using SPSS Version 21. The result showed that Return On Asset had no Significant effect on The growth profit of Shria Bank Negara Indonesia,has not been able to increase profit show that asset managemet